Contemporary Western historiography theories and concepts as the theoretical framework for the Soviet gender order formation in Kazakhstan, 1920-1930 (Journal of history, 2020)
The article deals with the most promising Western scholars theoretical constructs for the analysis of the transformation of gender discourse in the early Soviet period essence. Western scholars such Concepts as the gender order, gender roles and patriarchal bargain will allow us to insert a change of gender order in Kazakhstan into the Soviet project of social construction of masculine and feminine. The analytical potential of these constructs will allow us to uncover the cultural and symbolic, social and institutional as well as individual-psychological level of formation of the Soviet gender identity. The authors argue that the Western authors works and the theoretical framework presented in them allow to enrich the national science with new research strategies in the field of gender / women’s studies. Key words: gender order, gender roles, patriarchal bargain, classical patriarchy.